2011
DOI: 10.1371/journal.pone.0016175
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Respiratory Aeroallergen Exposure in Mice Induces Epithelial-Mesenchymal Transition in the Large Airways

Abstract: Chronic allergic asthma is characterized by Th2-polarized inflammation and leads to airway remodeling and fibrosis but the mechanisms involved are not clear. To determine whether epithelial-mesenchymal transition contributes to airway remodeling in asthma, we induced allergic airway inflammation in mice by intranasal administration of house dust mite (HDM) extract for up to 15 consecutive weeks. We report that respiratory exposure to HDM led to significant airway inflammation and thickening of the smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 35 publications
7
91
1
Order By: Relevance
“…Other epithelial cells co-expressing vimentin were found in the subepithelial region. These results suggest that EMT is implicated in the bronchial remodelling associated with asthma [129]. This is in agreement with previous reports demonstrating that exposure of epithelial cells to proteolytically active allergens such as Der p 1, a major mite allergen [64,130], or to some pollen allergens [131] induced the degradation of the epithelium.…”
Section: Emt In Chronic Bronchial Diseases Emt and Allergic Asthmasupporting
confidence: 93%
See 2 more Smart Citations
“…Other epithelial cells co-expressing vimentin were found in the subepithelial region. These results suggest that EMT is implicated in the bronchial remodelling associated with asthma [129]. This is in agreement with previous reports demonstrating that exposure of epithelial cells to proteolytically active allergens such as Der p 1, a major mite allergen [64,130], or to some pollen allergens [131] induced the degradation of the epithelium.…”
Section: Emt In Chronic Bronchial Diseases Emt and Allergic Asthmasupporting
confidence: 93%
“…Yet in combination with TGF-b, it enhances the expression of EMT markers. These results highlight the importance of TGF-b in EMT in asthma [64,129] and elevated levels of TGF-b have been reported in BAL and bronchial biopsies of asthmatic patients [132,133]. The increase of TGF-b correlates with airflow obstruction and airway wall thickening, and is not changed despite oral treatment with corticosteroids [134,135].…”
Section: Emt In Chronic Bronchial Diseases Emt and Allergic Asthmamentioning
confidence: 66%
See 1 more Smart Citation
“…90,91 Different reports suggest that EMT is linked to airway remodeling in asthma. 70,92 Interestingly, EMT is regulated by the Wnt/β-catenin and the noncanonical Wnt signaling pathway. [93][94][95] Also in the lung, Wnt signaling is involved in the regulation of EMT.…”
Section: Role Of Wnt Pathways In Airway Remodelingmentioning
confidence: 99%
“…Hackett et al suggested that the number of airway epithelial cells undergoing EMT is enhanced and that the process of epithelial repairs is dysregulated in bronchial asthma [14]. Johnson et al reported that house dust mite exposure induces EMT in large airways in mice [15]. These findings suggest that TGF-b1 released by eosinophils may induce EMT leading to airway remodelling.…”
Section: Introductionmentioning
confidence: 99%